Leveraging Artificial Intelligence for E-Commerce: Enhancing Personalization, Fraud Detection, and Customer Experience - Sambasiva Rao Akkisetti (International Journal of Intelligent Systems and Applications in Engineering, 2025)
The explosive growth of e-commerce has transformed consumer attitudes, driving a need for more sophisticated mechanisms to improve customer experience, personalize services, and provide secure engagement. AI has become a transformative tool in overcoming these challenges by optimizing personalization, identifying fraud, and increasing customer satisfaction. This paper highlights the role of AI in transforming e-commerce and emphasizes the significance of using predictive analytics, recommendation systems, and targeted marketing to customize shopping experiences. Additionally, it explores AI-powered fraud prevention methods, such as machine learning algorithms and anomaly detection, to counter the growing cybersecurity risk and financial fraud in online platforms. AI impacts customer experience through sentiment analysis, real-time customer support among other aspects. This paper presents a case study by identifying current trends and demonstrating how AI is capable of sending vibrations signals under the trends of e-commerce virtualization and digitization, which would eventually lead to a safer, more personalized, and engaging online shopping experiences for consumers. It concludes with future research directions, emphasizing the role of AI in the future of e-commerce.